A search for HI in nine southern galactic clusters - Olano, Carlos Alberto (1980)
The results of a search for H I features in nine galactic clusters are reported. In six of the clusters the earliest spectral types represented are in the range B0–B9. On the whole, twelve H I features (nine maxima and three minima) were detected, of which seven were disregarded as they were not related to any cluster. The conclusion is that at least in six clusters (Cr 121, Cr 140, Cr 132a, b, Ru 3 and Ru 106) no related H I could be detected. For the remainder (NGC 5460, Cr 135 and Cr 394), the evidence was inconclusive. Our results are in agreement with the qualitative conclusion from earlier work that interstellar H I should be expected only in relatively young clusters.